Strategic capitalism : - Calder, Kent E. (Princeton University press, 1993)
Was Japan's economic miracle generated primarily by the Japanese state or by the nation's dynamic private sector? In addressing this question, Kent Calder's richly detailed study offers a distinctive reinterpretation of Japanese government-business relations. Calder challenges popular opinion to demonstrate how Japanese private enterprise has complemented the state in achieving the national purpose of industrial transformation.